The Influence of the Taylor Rule on US Monetary Policy - Pelin Ilbas; Øistein Røisland; Tommy Sveen (Norges Bank, 2013)
We analyze the influence of the Taylor rule on US monetary policy by estimating the policy preferences of the Fed within a DSGE framework. The policy preferences are represented by a standard loss function, extended with a term that represents the degree of reluctance to letting the interest rate deviate from the Taylor rule. The empirical support for the presence of a Taylor rule term in the policy preferences is strong and robust to alternative specifications of the loss function. Analyzing the Fed's monetary policy in the period 2001 - 2006, we find no support for a decreased weight on the Taylor rule, contrary to what has been argued in the literature. The large deviations from the Taylor rule in this period are due to large, negative demand-side shocks, and represent optimal deviations for a given weight on the Taylor rule.
hdl:11250/2496706
Keywords: E42; E52; E58; E61; E65; 330; optimal monetary policy; simple rules; central bank preferences